Symposium 4: Innovative approaches to professional development: Symposium Introduction - Macdonald, Janet (Proceedings of the International Conference on Networked Learning, 2010)
Professional development at university is traditionally delivered through events, which might be complemented by texts or websites. However the challenge is to ensure that staff engage with the materials, and carry away something which is of value, and which can be embedded into practice when the practitioner is faced with a host of competing priorities. In the field of academic development, although not necessarily online, Boud (1999) has underlined the significance of approaches which are of obvious relevance to staff because they are situated or embedded within the working practices, and peer learning has clear benefits in this regard. In this context Knight, Tait and Yorke (2006) describe the relevance of Engestrom’s (2001) activity system, which provides a graphic illustration of the interplay between the specialist in educational development, the practitioner who might learn how to enhance their practice, and a range of influences including the people with whom they work, departmental policies, tools to cast understanding into practical shapes, and the division of labour within the department. Knight, Tait and Yorke described two studies of professional development at the Open University (UK) which were undertaken in 2004. They showed that while more formal approaches were involved where staff were expected to take on a specific role, non-formal and social learning, including “on-the-job” learning, conversations with colleagues and their own experiences as students had dominated the process of general professional formation. Such findings provide food for thought: clearly the process of embedding theory into good practice can be problematic and does not simply depend on the effective design of a professional development seminar. The focus for the papers in this symposium is on the significance of the context of practitioners when designing effective provision for professional development. This understanding allows innovations in learning and teaching practice to be situated and embedded within the practical circumstances of the individual, while providing and supporting non-formal or social learning. These ideas are illustrated with a discussion of the environment at the Open University and the distinctive ways in which staff work together within that environment, followed by three case studies of innovative professional development initiatives which showcase the deployment of experiential or peer learning to support the adoption of innovative practice. The Open University has a long and successful history in high quality distance education which has been underpinned by extensive use of online technologies over the last twenty years. With a rapidly increasingly pace of change, there is a pressing need to keep staff regularly updated with new working practices in learning and teaching. At the same time, the demands of delivering education at scale places specific demands on its staff, who work in ways which may be unfamiliar to traditional campus based institutions. This paper describes the working contexts and communities of staff at the university in order to provide an understanding of the constraints and opportunities for supporting successful professional development both in formal courses and resources and within informal networks. The Centre for Open Learning in Mathematics, Science, Computing and Technology (COLMSCT) was established to reward teaching excellence and fund practitioner research to develop effective and engaging ways of using new technologies to support students at a distance. In this paper COLMSCT is presented as a case study of professional development through practitioner research in order to illustrate how the theory of experiential learning can help in understanding the processes and outcomes of that professional development. The Digilab is a creative, informal space which enables Open University staff to experiment with technologies which have the potential to enhance learning. A series of ‘Digiquests” were developed which require staff to use a variety of accessible devices and immersive environments to support reflective learning. The resulting activities form a suite of self paced and collaborative opportunities to encounter some of the key issues, constraints and possibilities for developing technology enhanced experiential learning for learners and practitioners within a safe and neutral space. Finally we describe a case study of two short online courses at the Open University which set out to provide professional development in online communities of distance tutors. They operate at scale: in 2009, 1000 staff have participated in the courses. The course design on both courses have in different ways supported experiential learning with opportunities for discussion and peer support, while at the same time offering some flexibility in participation. The paper discusses some of the lessons we have learnt from participants on the reasons for the success of these initiatives and the factors influencing effective engagement.